2002
DOI: 10.1074/jbc.m202883200
|View full text |Cite
|
Sign up to set email alerts
|

Novel Binding of HuR and Poly(C)-binding Protein to a Conserved UC-rich Motif within the 3′-Untranslated Region of the Androgen Receptor Messenger RNA

Abstract: The interaction between androgens such as dihydrotestosterone (DHT) 1 and the androgen receptor (AR) plays a crucial role in the evolution of human prostate cancer, and modulation of this interaction represents a major therapeutic strategy (1, 2). The biological action of androgen is mediated via binding to the AR, a member of the nuclear hormone receptor family of transcription factors that regulate expression of androgen-responsive genes (3). Androgens promote the growth of prostate cancer cells, and androge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
154
1
2

Year Published

2004
2004
2014
2014

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 129 publications
(161 citation statements)
references
References 51 publications
4
154
1
2
Order By: Relevance
“…12 The NMR titration data herein reported and earlier findings with HuB, 59 demonstrate that isolated RRM3 can bind to AREs, although previous studies suggested a negligible role of HuR RRM3 ¡ as part of HuR FL ¡ in AREs recognition. 34,[44][45][46] Isolated RRM3 is in a monomer/dimer exchange on a time scale unfavorable for NMR observation of the residues at the dimerization site, notably those in the W261-T271 region at the C-end of helix a 1 . Indeed, this region shows large fluctuations in MD simulations, which affect the H-bonding pattern at a 1 and the dynamics of W261 ring.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…12 The NMR titration data herein reported and earlier findings with HuB, 59 demonstrate that isolated RRM3 can bind to AREs, although previous studies suggested a negligible role of HuR RRM3 ¡ as part of HuR FL ¡ in AREs recognition. 34,[44][45][46] Isolated RRM3 is in a monomer/dimer exchange on a time scale unfavorable for NMR observation of the residues at the dimerization site, notably those in the W261-T271 region at the C-end of helix a 1 . Indeed, this region shows large fluctuations in MD simulations, which affect the H-bonding pattern at a 1 and the dynamics of W261 ring.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, isolated HuR RRM3 preferably binds U-rich versus AU-rich RNA stretches, despite previous studies suggesting that RRM3 has a negligible contribution to ARE-binding events in comparison with the other 2 HuR RRM motifs. 34,[44][45][46] Although the HuR linker between RRM2 and RRM3 could contribute to the ARE stabilization, 34,35 it was unfeasible to obtain a linker-bearing RRM3 construct in a soluble manner. Moreover, HuR RRM3 phosphorylation, which was mimicked by a S318-to-D318 substitution, causes no significant structural changes of RRM3, in contrast to a phosphorylation-mediated unfolding described in other types of RNA domains.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…GST Fusion Protein Preparation-Purified recombinant ␣CP1 from PreScission protease-cleaved GST-␣CP1 fusion protein was prepared as described previously (18). Briefly, 1-liter cultures of Escherichia coli DH5␣ expressing GST or GST-␣CP1 fusion constructs (described in Ref.…”
Section: Interleukin-1 Control Of H-ferritin Translationmentioning
confidence: 99%
“…The poly(C)-binding proteins (PCBPs) are a structurally diverse family, including heterogeneous nuclear ribonucleoprotein K and ␣CP1-4 (17). They bind mRNA sequences that contain either a single C run (heterogeneous nuclear ribonucleoprotein K) or stretch of C's (␣CPs) via their K-homology (KH) domains (18). The PCBPs have been implicated in regulation of mRNA stability, translation silencing (mainly through interactions with 3Ј-UTR sequences), and enhancement.…”
mentioning
confidence: 99%